2023
DOI: 10.3345/cep.2023.00290
|View full text |Cite
|
Sign up to set email alerts
|

Association between dyslipidemia and asthma in children: a systematic review and multicenter cohort study using a common data model

Abstract: Background: The association between dyslipidemia and asthma in children remains unclear.Purpose: This study investigated the association between dyslipidemia and cholesterol levels in children.Methods: A systematic literature review was performed to identify studies investigating the association between dyslipidemia and asthma in children. The PubMed database was searched for articles published from January 2000–March 2022. Data from a cohort study using electronic health records from 5 hospitals, converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In the present study, we found that children with VSD were not significantly more frequently admitting asthma than non-VSD. This disagreement might be because asthma results from complex gene-environment interactions with heterogeneity in clinical presentation 23 , 24 . One study has demonstrated a high prevalence of airway hyperresponsiveness in patients with ASD, suggesting that airway hyperresponsiveness might be a possible mechanism for recurrent attacks of cough variant asthma 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that children with VSD were not significantly more frequently admitting asthma than non-VSD. This disagreement might be because asthma results from complex gene-environment interactions with heterogeneity in clinical presentation 23 , 24 . One study has demonstrated a high prevalence of airway hyperresponsiveness in patients with ASD, suggesting that airway hyperresponsiveness might be a possible mechanism for recurrent attacks of cough variant asthma 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 37 Furthermore, dyslipidemia could be associated with an increased risk of asthma. 38 This may have resulted in overestimation of the effect of the apoB/apoA-I ratio on lung function. Additionally, the previous study adjusted for only a few variables In contrast, we only included asymptomatic healthy subjects and minimized potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed for the multicenter analysis of disparate databases. This consisted of the following information: person, drug exposure, drug era, condition occurrence, condition error, observation period, observation, procedure occurrence, visit occurrence, death, drug cost, procedure cost, location, provider, organization, care site, payment plan period, and cohort ( 26 ). The analysis period and total number of patients were 2003 to 2020 and 880,392 from MJ, 2006 to 2017 and 822,183 from KH, 2006 to 2019 and 2,363,386 from CHA, and 2011 to 2018 and 1,753,001 from PS.…”
Section: Methodsmentioning
confidence: 99%